2020
DOI: 10.1016/j.lungcan.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy of combinatorial therapy of EGFR-TKI and crizotinib in overcoming MET amplification-mediated resistance from prior EGFR-TKI therapy

Abstract: Background: : MET amplification is one of the EGFR-independent mechanisms of EGFR tyrosine kinase inhibitor (TKI) resistance. Combinatorial therapy of EGFR-TKI and crizotinib has been explored as a strategy to overcome resistance by simultaneously targeting both EGFR and MET pathways; however, no consensus still exists on the optimal combination regimen with the most benefit. Methods: : Retrospective analysis was performed on the clinical and sequencing data obtained from eleven patients with lung adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
0
29
2
Order By: Relevance
“…Still now, the resistance of the gefitinib mechanism is confusing. Gefitinib-resistant (GR) patients manifest many pathways abnormal activation, including MET/HER2 amplification, activation of the RAS-mitogen-activated protein kinase (MAPK)-ERK, or RAS-phosphatidylinositol 3-kinase (PI3K)-AKT pathways ( 27 29 ). In this study, we found that PC9-GR cells showed a high expression of RhoV, which means RhoV might associate with GR circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…Still now, the resistance of the gefitinib mechanism is confusing. Gefitinib-resistant (GR) patients manifest many pathways abnormal activation, including MET/HER2 amplification, activation of the RAS-mitogen-activated protein kinase (MAPK)-ERK, or RAS-phosphatidylinositol 3-kinase (PI3K)-AKT pathways ( 27 29 ). In this study, we found that PC9-GR cells showed a high expression of RhoV, which means RhoV might associate with GR circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there is still no consensus on the optimal subsequent-line treatment regimen for patients who acquired MET amplification-mediated EGFR-TKI resistance. The efficacy of crizotinib either alone or in combination with any EGFR-TKI has been explored among patients who were detected with MET amplification after progression from EGFR-TKI treatment (16,19,20,22,36,37). Due to the limited sample size, the data in these studies were inadequate to strongly support the standard clinical use of combination therapies targeting both EGFR and MET after MET amplification-mediated EGFR-TKI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The reciprocal crosstalk between EGFR and MET in lung adenocarcinoma suggests that simultaneous inhibition through the combined use of EGFR-TKI and MET-TKI would benefit and potentially improve the survival outcomes of patients with concurrent EGFR and MET aberrations (17,18). Over the years, a growing number of studies have demonstrated the clinical benefit of different combinations of various generations of EGFR-TKIs and various MET-TKIs including crizotinib (16,(19)(20)(21)(22)(23), capmatinib (21,24), and savolitinib (25)(26)(27). Recently, tepotinib plus gefitinib showed promising antitumor activity in NSCLC with concomitant EGFR mutation and MET amplification or high MET overexpression compared with chemotherapy (28).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated MET copy number amplification in this patient may be a resistance mechanism to EGFR‐TKI. Combination therapy has been reported to have a better overall response rate (ORR), progression‐free survival (PFS) and overall survival (OS) in patients than monotherapy, 1,2 although there have been some successful reports of crizotinib monotherapy in EGFR ‐mutant NSCLC that acquired MET amplification.…”
Section: Discussionmentioning
confidence: 99%